2015
DOI: 10.1186/s12890-015-0042-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of microbial agents in dust and respiratory health in the Ecrhs

Abstract: BackgroundDampness and mould exposure have been repeatedly associated with respiratory health. However, less is known about the specific agents provoking or arresting health effects in adult populations. We aimed to assess predictors of microbial agents in mattress dust throughout Europe and to investigate associations between microbial exposures, home characteristics and respiratory health.MethodsSeven different fungal and bacterial parameters were assessed in mattress dust from 956 adult ECRHS II participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…To our knowledge, there is only 1 comparable study which investigated the associations between microbial exposures measured in the home environment with respiratory disorders in adults. A recent study that had its population also drawn from the ECRHS II cohort reported an association of higher levels of muramic acid in mattress dust with the asthma symptom score, an effect opposite to the current findings. Tischer et al utilized a population of 956 subjects in 22 centers from 10 countries, whereas our current study analyzed 397 study subjects from 14 centers located in 7 countries in an asthma case‐control design; the 2 study populations did not overlap as concerns the study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, there is only 1 comparable study which investigated the associations between microbial exposures measured in the home environment with respiratory disorders in adults. A recent study that had its population also drawn from the ECRHS II cohort reported an association of higher levels of muramic acid in mattress dust with the asthma symptom score, an effect opposite to the current findings. Tischer et al utilized a population of 956 subjects in 22 centers from 10 countries, whereas our current study analyzed 397 study subjects from 14 centers located in 7 countries in an asthma case‐control design; the 2 study populations did not overlap as concerns the study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…This study did not include any objective measurements of microbial markers in household dust. However, geographical and domestic determinants of the concentration of microbial components (endotoxin, muramic acid, and bacterial and fungal DNA) in dust collected from the bed have been analyzed in two recent publications based on a subset of the ECRHS study …”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that there was a correlation between dog allergen and bacterial components in dust in our study and that the bacterial compounds could have immune-modulating properties lowering FeNO levels. Dog keeping is associated with increased levels of various bacterial components in home dust, including mycobacteria species DNA, gram positive bacteria DNA, gram negative bacteria DNA and muramic acid, an indicator of gram-positive bacteria (Tischer et al, 2015). Moreover, dogs can be a source of endotoxin in home dust (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%